Organic Rankine cycle design and performance comparison based on experimental database. (15th October 2017) - Landelle, Arnaud; Tauveron, Nicolas; Haberschill, Philippe; Revellin, Rémi; Colasson, Stéphane
Highlights: An open-access database of ORC experiments is presented and released. ORC main parameters are discriminated and harmonized in the database frame. A selection of simplified ORC thermodynamic performance criteria is proposed. Database analysis shows actual Organic Rankine Cycle state-of-the-art performances. A statistical method for ORC performances analysis and comparison is introduced. Abstract: The Organic Rankine Cycle (ORC) is a technology commonly used for low-grade thermal energy conversion in electricity. This technology is mature for large power scale and last research focused on small scale units for domestic or onboard applications. This paper presents an extensive open-access database of more than 100 ORC experiments collected from about 175 scientific literature references. Data harmonization and database frame are presented. Clear and consistent components and ORC performance criteria are proposed and applied to the data set of various ORC. An overview of the ORC experimental state-of-the-art is displayed and major trends are drawn. Efficiency of key components such as expanders and pumps are analyzed and used for ORC parametric optimization case study. Correlations of some parameters with ORC performances are statistically investigated, performance improvement of novel fluid or cycles is evaluated.